МАРКЕТИНГОВЫЙ ИНСТРУМЕНТАРИЙ ИССЛЕДОВАНИЯ РЫНКА ТРУДА В ТРУДОИЗБЫТОЧНЫХ РЕГИОНАХ (Journal of Economic Research & Business Administration, 2016)
It is theory of marketing instrumetariya as applied to labour market. It is describes the specificity of marketing educational services market.